How to boost and reach the full potential of Mugler-s perfumes brand loyalty? - an analysis of Mugler-s refill value proposition in Portugal - Oberlohr, Madeleine (2022)
The main purpose of this work project is to analyze Mugler's capacity to boost and reach the full potential of its perfumes brand loyalty to retain consumers in Portugal further. Beyond desk research, 30 in-depth interviews with Mugler consumers, social media listening, and mystery client were conducted. As a result, three Mugler consumer segments were identified, and the potential of the loyalty drivers and the relationship with the brand were evaluated. Furthermore, the refill concept as one main driver has been further analyzed. The derived recommendations, including online and offline implications, enable Mugler to enhance its refill value proposition.